ORIENTASI NILAI BUDAYA DI KALANGAN PEREMPUAN TERHADAP MODEL PAKAIAN DI KOTA MANADO - Bagit, Vini Fitriana (HOLISTIK, Journal Of Social and Culture, 2017)
Clothes that we use could display all function. As form of communication,clothing can convey a message artifaktual that is nonverbal. Clothing to protectus from severe weather or in a particular sport from the possibility of injury.Clothes lead us to hide certain parts of our bodies and hence of a garment hasa function civility (modesty function). Phenomena the development of fashionbe a hot growing trend in Manado of shorts (look sexy), hooded but use shirtsand pants lagging who tight that it reflects indentations his body (jilboob).This research chose to use research methodology qualitative to determine tofind, gather, process and analyzed data the outcome of this research. Thequalitative study can be used to understand social interaction, for example byin-depth interviews so that it will found patterns clear.Fashion express an identity a particular figure, then the outfit is one of a wholerange of labelling the most obvious of the outward appearance of a person.Manado is currently showing rapid progress in life style, especially in the field offashion. The demands of an increasingly modern times as well as the influenceof Association and job demands have forced most of the women in the town ofManado follows the style of dress which became a trend in the desire whichindicates the occurrence of a shift in cultural values how to dress as well as thedecline in moral values from the custom of â€œeasternâ€ embraced by this nation.Keyword: life style, fashion, value